Pengetahuan Ibu tentang Manfaat Bermain pada Perkembangan Anak Usia balita di Masa Pandemi Covid-19 - Rosa Melati; Metha Kemala Rahayu (Nursing News : Jurnal Ilmiah Keperawatan, 2021)
During the Covid-19 pandemic, the government implemented the PSBB (Large-Scale Social Restrictions), which meant that no outdoor activities for the community, including children. Children's activities in the surrounding environment experience changes and restrictions. The design of this study was an analytic design with a cross sectional approach. The population of this study were all mothers who have children aged 1-5 years in Jatiluhur, and a sample of 50 respondents. The data collection tool was a questionnaire. Univariate and bivariate data analysis using the Spearmen Rank correlation. The results of this study are that the majority of the mother's knowledge level about the benefits of playing for toddlers (aged 1-5 years) is in the good category (42 mothers: 87.5%) and the development of toddlers (ages 1-5 years) the majority is in the normal category of 59 people ( 94.5%). It is shown by the results of statistical tests using the Spearmen Rank with z count 3.181 z table (1.96). The conclusion from this study is that there is a relationship between the level of maternal knowledge about the benefits of playing with the development of toddlers (ages 1-5 years). Keywords: benefits of playing, knowledge, development